The tensile performance of r-PET bottle string: effects of different string sizes and cutting axes - Nasir, Khairani; Abdul Rashid, Azrin Hani; Abd. Razak, Nurul Atikah; Shaari, Muhammad Farid; Roslan, Mohd Nazrul; Shamsudin, Shazarel; Ansar, Mohd Shukri; Husain, Siti Nor Hawanis; Dzulkefli, Syafiqah; Marsi, Noraini (Horizon Research Publishing, 2019)
Recently, plastic waste has become one of the global issues which contributes to severe environmental pollution and threatens marine life as it takes a longer time to decompose. This study was aimed to protect the environment by recycling waste materials to reduce solid wastes. Recycled polyethylene terephthalate string was used in the study to identify tensile properties. The main aim of this research was to identify the tensile strength properties by investigating different string sizes for the r-PET bottle (4 mm, 5 mm, and 6 mm) at different cutting axes (horizontal and vertical). According to ASTM D882-02, the tensile strength test was conducted with a load cell of 50 N and crosshead speed of 50 mm/min at room temperature. To reduce the possibility of nuisance factors that will affect the result, five repetitive tests were carried out and Minitab R.18 software was used to analyse the obtained data. Results revealed that the 4 mm string in both cutting axes demonstrated the highest strength of tensile performance and modulus elasticity.